The Authorship of Two Girls on a Barge (1891), Reassessed - Huenemann, Karyn (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2020)
Until recently, the novel Two Girls on a Barge (1891) has been attributed to Canadian author and journalist Sara Jeannette Duncan (1861–1922), writing under the pseudonym “V. Cecil Cotes.” This article provides evidence that, while Duncan did appear to have influenced the style and structure of the novel, the author was Violet Cecil Cotes (1868–1915), Duncan’s sister-in-law.